Age ultrastructural features of sclera in intact rats. - Ulyanova, N. A.; Dumbrova, N. E.; Molchanyuk, N. I. (Морфологія / Morphologia / Morfologìâ, 2013)
Background. The absence of adequate experimental myopia model is the actual problem in pathophysiological studying of the myopia progression. Studies of the chick eye have formed the basis for several hypotheses of myopic development. The most pathogenesis reasonable myopia animal model is a form-deprivation myopia in chicks. The introduction of form-deprivation myopia animal model in mammals in particular rats, is necessary to study the dynamics of age morphological changes in sclera. Objective. To examine age-related features of the sclera in intact rats on the ultra-structural level. Methods. It was investigated the sclera ultrastructure by using electron microscopy method in intact rats at 14, 21, 30, 90 days. Results. It was set that in rats’ eyes at the age of 14-21 days the sclera presence of fibroblasts, characterizing the active generation of plastic materials, mainly on collagen. At the age of 30-90 days, the number of fibroblasts decreases and normal cells become mature look. However, practically, in all study periods, but with advantage aged 14-21 days, some of the cells are eliminated by apoptosis. At the age of 14-21 days is not formed clear scleral tissue architecture, part of the collagen fibrils stacked in bundles, part loosely arranged. At the age of 90 days, collagen scleral stroma is ordered. Conclusion. We identified a significant amount of fibroblasts decreasing, fibroblasts functional activity reduction, and collagen fibers ordering in sclera of the intact rats during the period from 14 to 90 days of postnatal ontogenesis. The highest intensity of the restructuring in the sclera is observed between 14-30 days of postnatal ontogenesis. In our opinion, this period is optimal for experimental modeling myopia in rats.